Do BRCA1/2 mutation carriers have an earlier onset of natural menopause?. Issue 8 (August 2016) - van Tilborg, Theodora C.; Broekmans, Frank J.; Pijpe, Anouk; Schrijver, Lieske H.; Mooij, Thea M.; Oosterwijk, Jan C.; Verhoef, Senno; Gómez Garcia, Encarna B.; van Zelst-Stams, Wendy A.; Adank, Muriel A.; van Asperen, Christi J.; van Doorn, Helena C.; et al.
Abstract: Objective: It has been hypothesized that BRCA1/2 mutation carriers have an earlier age at natural menopause (ANM), although to date findings are inconclusive. This study assessed the influence of BRCA mutation status on ANM, and aimed to explore the reasons of inconsistency in the literature. Methods: Cross-sectional assessment from an ongoing nationwide cohort study among members of BRCA1/2 mutated families. Information was obtained by a standardized questionnaire. Kaplan-Meier curves were constructed, and Cox regression was used to assess the association between BRCA1/2 mutation status and ANM. Adjustments were made for birth cohort, family, smoking, use of hormonal contraceptives, and parity. Results: A total of 1, 208 BRCA1/2 mutation carriers and 2, 211 proven noncarriers were included. Overall, no association was found between BRCA1/2 mutation status and ANM (adjusted hazard ratio [HR] = 1.06 [95% CI, 0.87-1.30]). We examined if the null finding was due to informative censoring by uptake of risk-reducing salpingo-oophorectomy. Indeed, within the oldest birth cohort, in which the percentage of surgical menopause events was lowest and comparable between carriers and noncarriers, the HR for earlier natural menopause in carriers was 1.45 (95% CI, 1.09-1.94). The second oldest birth cohort, however, demonstrated a decreased HR (0.67 [95% CI, 0.46-0.98]), and thus no trend over birth cohorts was found. Conclusions: Various types of selection bias hamper the comparison of ANM between BRCA1/2 mutation carriers and noncarriers, genetically tested in the clinic. Abstract : Supplemental Digital Content is available in the text